2010
DOI: 10.1111/j.1551-2916.2010.04229.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Magadiite/Si‐ZSM‐11 Composites

Abstract: The simplified one‐step hydrothermal synthesis, in which SiO2 is directly reacted with aqueous NaOH in the presence or absence of tetrapropylammonium bromide (TPABr) and tetrabutylammonium bromide (TBABr) as the template compound, was investigated. The reaction in the absence of the template compounds leads to the production of pure magadiite, whereas pure Si‐ZSM‐5 is produced by the reaction in the presence of TPABr. On the other hand, crystalline magadiite/Si‐ZSM‐11 composites are synthesized by the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The mechanism for the formation of the ZSM-5/magadiite compounds is not fully understood, as it is not necessary to use any SDA to obtain magadiite. Several studies report the synthesis of magadiite, where the ratio SiO 2 :NaOH has been in the range of 1:0.2 to 1:9 [31][32][33][34][35][36]. The ratio of Na 2 O species in the lamellar region needed to be higher than in the zeolite region to induce the hydrolysis of highly silicic aluminosilicate species to magadiite [37].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism for the formation of the ZSM-5/magadiite compounds is not fully understood, as it is not necessary to use any SDA to obtain magadiite. Several studies report the synthesis of magadiite, where the ratio SiO 2 :NaOH has been in the range of 1:0.2 to 1:9 [31][32][33][34][35][36]. The ratio of Na 2 O species in the lamellar region needed to be higher than in the zeolite region to induce the hydrolysis of highly silicic aluminosilicate species to magadiite [37].…”
Section: Resultsmentioning
confidence: 99%
“…A Figura 1(b) apresenta os difratogramas das amostras sintetizadas com misturas binárias de TEAOH e isobutilamina, os quais demonstraram que em todos os períodos de cristalização são obtidos materiais com a coexistência da fase da ZSM-5 (JCPDS Nº 42-0023) e a da fase lamelar Magadiita. Estudos relatam a síntese da Magadiita, com a proporção SiO 2 : NaOH na faixa de 1,0 : 0,2 a 1,0 : 9,0, onde a proporção SiO 2 : NaOH utilizada neste trabalho foi de 1,0 : 0,3, podendo então a quantidade de NaOH utilizada ter favorecido a formação da magadiita, levando à formação de várias áreas segregadas classificadas em regiões zeolíticas e lamelares (Ozawa et al, 2010, Xu et al, 2015.…”
Section: Resultados E Discussõesunclassified
“…However, in the absence of TBA þ , ZSM-11 cannot be synthesized with SiO 2 as silica source. Instead, pure magadiite was produced [37]. Of course, it has been found that the ZSM-11 zeolite synthesized with TBAOH as template is actually a ZSM-11/5 composite or intergrowth [25].…”
Section: Introductionmentioning
confidence: 99%